The Politics of Legitimacy: The Accounts of Pakubuwana IX and Kiai Abdul Qohhar on Kidung Sesingir - Minardi, Minardi; Nisa, Kanita Khoirun (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to determine the relationship of Kiai Abdul Qohhar Ngruweng and Pakubuwana IX in Javanese poem, Kidung Sesingir. Using the literature study method and field interviews, it was found that the relationship of ulama and political ruler in Java always had ups and downs from the time before the emergence of Islam until the establishment of Republic of Indonesia. There are many factors in the background, but legitimacy is the dominant one. Several stanzas in Kidung Sesingir show the importance of Kiai Abdul Qohhar Ngruweng to Pakubuwana IX, particularly regarding political legitimacy. Even though the existence of the ulama is fading, Pakubuwana IX still uses the existence of the ulama as a form of legality. The legitimacy is in the form of a sentence that Kiai Abdul Qohhar Ngruweng knows the history of the genealogy of the Prophet Muhammad until Pakubuwana IX. For a Muslim Mataram king in Java, it is essential to show that the king is also a descendant of the Prophet Muhammad. Meanwhile, Kiai Abdul Qohhar Ngruweng is a descendant of Tembayat network from Sunan Pandanaran, who, together with Sunan Kajoran, were then the counter-elite for the Mataram dynasty.